1995
DOI: 10.1002/dc.2840130305
|View full text |Cite
|
Sign up to set email alerts
|

Atypical endocervical glandular cells: Accuracy of cytologic diagnosis

Abstract: Atypical cells thought to be of endocervical glandular origin often cause diagnostic uncertainty in cervicovaginal smears. For this reason consecutive cases of endocervical glandular atypia diagnosed in smears were correlated with subsequent biopsy diagnoses and then retrospectively reviewed. Smears were originally diagnosed as "mild glandular atypia, probably reactive" or "severe glandular atypia, suggestive of adenocarcinoma in situ" (AIS). Biopsy follow-up was obtained on 34 of 58 patients diagnosed with se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
86
2
5

Year Published

1997
1997
2002
2002

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 98 publications
(105 citation statements)
references
References 7 publications
(2 reference statements)
9
86
2
5
Order By: Relevance
“…The PPVs for the endocervical AGUS subcategories demonstrated a marked difference between the "favor neoplasia" designation and either the "unspecified" or "favor reactive" designations in both types of preparations (67% vs. 28% vs. 10% in TPs and 77% vs. 23% vs.4% in CPs). These differences are similar to those reported in other studies of biopsy follow-up results after an AGUS interpretation in CPs, [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] and in one similar study using TPs, 20 and demonstrate that differences in PPVs among endocervical AGUS subcategories are similar in both TPs and CPs. Although the number of cases was small, we found that the AGUS "endometrial" category had a very low PPV in both groups.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The PPVs for the endocervical AGUS subcategories demonstrated a marked difference between the "favor neoplasia" designation and either the "unspecified" or "favor reactive" designations in both types of preparations (67% vs. 28% vs. 10% in TPs and 77% vs. 23% vs.4% in CPs). These differences are similar to those reported in other studies of biopsy follow-up results after an AGUS interpretation in CPs, [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] and in one similar study using TPs, 20 and demonstrate that differences in PPVs among endocervical AGUS subcategories are similar in both TPs and CPs. Although the number of cases was small, we found that the AGUS "endometrial" category had a very low PPV in both groups.…”
Section: Discussionsupporting
confidence: 89%
“…[2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] In general, those laboratories that report lower AGUS frequencies have higher PPVs for the detection of a high-grade precursor lesion or carcinoma and for lesions found to have glandular rather than squamous differentiation on follow-up. 6,9,16 In contrast, laboratories with higher AGUS frequencies have shown a high preponderance of either benign processes or high-grade CIN on biopsy follow-up.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most laboratories report an AGUS rate Ͻ 1%. [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] The AGUS rate of 0.56% observed among the general patient population in our laboratory was in agreement with the current literature. Few studies have investigated the incidence of atypical endometrial cells in cervicovaginal smears.…”
Section: Discussionsupporting
confidence: 88%
“…[3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] Little is known about the clinical significance of AGUS, favor endometrial origin (AGUS-EM). In this retrospective study, we determined the rate of a diagnosis of AGUS-EM and the incidence of clinically significant lesions in women with this cytologic diagnosis on subsequent follow-up.…”
mentioning
confidence: 99%